2012
DOI: 10.2169/internalmedicine.51.8275
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-depleted Hodgkin Lymphoma Complicating Hemophagocytic Lymphohistiocytosis as an Initial Manifestation: A Case Report and Review of the Literature

Abstract: Hemophagocytic lymphohistocytosis (HLH) is commonly associated with infectious diseases or T/NK celllymphoma; however that with Hodgkin lymphoma (HL) was rarely reported. Herein, we describe a young male diagnosed with lymphocyte-depleted HL (LD-HL) complicated by HLH as an initial manifestation. He was given high-dose steroid therapy plus recombinant thrombomodulin, and subsequent ABVd (doxorubicin, bleomycin, vinblastine, dacarbazine) treatment. In spite of the achievement of a partial remission treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…Those reports revealed that the mixed cellularity type and lymphocytedepleted type are two major types of Hodgkin lymphoma that accompany HLH. In addition, most cases showed Epstein-Barr virus to be present in the Hodgkin cells or Reed-Sternberg cells (4,5,10). Consistent with these findings, the pathological diagnosis of our patient was the mixed cellularity type in which Reed-Sternberg cells were positive for EBER1 staining.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Those reports revealed that the mixed cellularity type and lymphocytedepleted type are two major types of Hodgkin lymphoma that accompany HLH. In addition, most cases showed Epstein-Barr virus to be present in the Hodgkin cells or Reed-Sternberg cells (4,5,10). Consistent with these findings, the pathological diagnosis of our patient was the mixed cellularity type in which Reed-Sternberg cells were positive for EBER1 staining.…”
Section: Discussionsupporting
confidence: 88%
“…Hodgkin lymphoma-associated HLH is rare with only a limited number of reported cases (3)(4)(5). Those reports revealed that the mixed cellularity type and lymphocytedepleted type are two major types of Hodgkin lymphoma that accompany HLH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although T cells lack CD21 receptor for the EBV entrance into the cells, EBV genome was present in T cell lymphomas and T lymphocytes from patients with HLH [12,13]. EBV driven T cell and NK-cell lymphomas are among the most common lymphoid neoplasms associated with the development of HLH [14]. On the other hand, B cell lymphomas are rarely associated with HLH development.…”
Section: Or At Least 3 Ofmentioning
confidence: 99%
“…Furthermore, the use of ABVD for cHL-associated HLH is associated with poor outcomes – in four reported cases, one recovered, one relapsed, and two died. [810,12] Therefore, the optimal treatment approach for cHL-associated HLH is not known. Notably, CEPP has been shown to be a well-tolerated and effective therapy in non-Hodgkin lymphoma and cHL, even in the setting of marked liver and renal dysfunction.…”
mentioning
confidence: 99%